Texture gradient in a copper tube at maximum and minimum wall thickness. Issue 1 (April 2015) - Brokmeier, H-G; Carradó, A; Al-hamdany, N; Pirling, T; Wimpory, R; Schell, N; Palkowski, H
Abstract: Tube drawing is an inhomogeneous process with anisotropic flow. Quantitative texture analysis was used to get inside in eccentricity and ovality of a Cu-tube drawn without a plug. To obtain the texture gradient over the wall thickness high resolution synchrotron radiation was used. One obtains on one hand different textures at the surfaces than in the central region and the other hand a variation of the texture gradient at the maximum wall thickness of the tube compared to the minimum wall thickness.